A Cu(II)-based coordination polymer: catalytic properties and treatment activity on stroke. Issue 1 (31st December 2022) - Gao, Peng-Ju; Liu, Ji-Rong
ABSTRACT: A fresh Cu(II) coordination polymer, i.e., [Cu3 (Hmbdc)2 (mbdc)2 (dmphen)2 ]n (1, H2 mbdc = isophthalic acid, dmphen = 4, 7-dimethyl-1, 10-phenanthroline), has been generated with the hydrothermal reactions between Cu salts and the mixed ligands of 4, 7-dimethyl-1, 10-phenanthroline and isophthalic acid. Moreover, the catalytic activity of 1 was evaluated via degrading the Congo red with a method of Fenton with an excellent degradation efficiency of 95.8% at 100 min. Next, the application value of compound on stroke was assessed, and the related mechanisms were explored at the same time. First of all, the tumor necrosis factor-α and recombinant rat IL-1β content released into the plasma were determined with enzyme-linked immunosorbent assay detection kit. Besides, the activation of the HMGB1/TLR4 signaling pathway activation in cerebral vascular endothelial cells was also determined with real-time reverse transcription–polymerase chain reaction assay.